Correlation of Left Atrial Size with Mitral Valve Area & Atrial Fibrillation in The Patients of Mitral Stenosis An Echocardiographic Based Study - ASIF HANIF, M.IMRAN HANIF, USMAN JAVED IQBAL, MAJID KALEEM, (Journal of Fatima Jinnah Medical University, 2018)
Background: Valve stenosis is a common heart disorder and an important cause of cardiovascular morbidity and mortality. Rheumatic heart disease (RHD) is the most common cause of mitral stenosis (M.S). It is most common in females as compared to males. Enlarged left atrium is the feature of mitral stenosis. In view of the associated lower survival valve diseases thus represent an important public health problem. Objective: To see how many patients of mitral stenosis have atrial fibrillation (A.F) and what is the relationship between left atrial size and mitral valve area. Methodology: This study was performed in the cardiology department of Gulab Devi Chest Hospital. We took the data of 50 patients. SPSS version 16.0 was used to evaluate the data. Descriptive statistics, bar charts and Pearson correlation test was used. Results: The mean age and BMI of the patients were 35±12.37 and 20.76 ± 3.87 respectively. Data showed females predominance. Out of 50 patients 46% had atrial fibrillation. Mean LA size was reported as 50.6±11.93mm with minimum and maximum range as 32mm and 100mm .The mean mitral valve area (MVA) was 0.84±0.17cm2 with minimum and maximum range as 0.6 and 1.5cm2. Echocardiographic investigations revealed that out of 50 patients 47 patients had pliable mitral valve, 2 patients had non pliable mitral valve, 25 had pulmonary hypertension and 6 patients had calcified valve. Pearson Correlation test shows a weak correlation (0.014) between left atrial size and mitral valve area with a p-value 0.926 which is insignificant. Conclusion: Frequency of M.S is more common in females as compared to males. Out of 50 patients 23 patients had atrial fibrillation (AFIB). RHD is the common risk factor in the patients of mitral stenosis and there is no correlation between LA Size and MVA.